2017
DOI: 10.1371/journal.pntd.0006070
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of dengue follows transportation infrastructure changes in the state of Acre, Brazil: A network-based analysis

Abstract: Human mobility, presence and passive transportation of Aedes aegypti mosquito, and environmental characteristics are a group of factors which contribute to the success of dengue spread and establishment. To understand this process, we assess data from dengue national and municipal basins regarding population and demographics, transportation network, human mobility, and Ae. aegypti monitoring for the Brazilian state of Acre since the first recorded dengue case in the year 2000 to the year 2015. During this peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 47 publications
(62 reference statements)
3
57
0
1
Order By: Relevance
“…disease [23]. While the network topology is characterized by centrality measures of the nodes (countries) in the air transport network.…”
Section: Introductionmentioning
confidence: 99%
“…disease [23]. While the network topology is characterized by centrality measures of the nodes (countries) in the air transport network.…”
Section: Introductionmentioning
confidence: 99%
“…One study in Acre, Brazil found that Ae. aegypti density and risk of dengue increased with tourism and case importation [202]. A study in Mexico City found a positive correlation between dengue incidence and Ae.…”
Section: Resultsmentioning
confidence: 99%
“…A vision capable of predicting the directions taken by the coronavirus involves scientific methodology that incorporates information generated by hundreds of studies 17 . Air traffic data and data on movement within Brazil's states allows simulating the epidemic's spread and orienting resource allocation 18 .…”
Section: Science During the Pandemicmentioning
confidence: 99%